PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KUALITAS LABA DAN NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DIBURSA EFEK JAKARTA) - Irianing Suparlinah; Indra Nurmanto; I Wayan Mustika (Solusi, 2020)
This research entitled is "Analyze the Influence of Corporate Governance Mechanism to Earning Quality and Value of the Firm (An Empirical Study on Manufacturing Companies at Jakarta Stock Exchange). The purpose of the research was to disclose first whether corporate governance mechanism (managerial ownership, board of commissioner composition and audit committee) influence earning quality. Second, whether corporate governance mechanism (managerial ownership, board of commissioner composition and audit committee) and earning quality influences value of the firm.Data used in this research was obtained from 78 manufacturing companies that enlisted in Jakarta Stock Exchange. Data was analyzed using structural equation model (SEM) with AMOS 5 software.Research Result that ( 1) corporate governance mechanism (managerial ownership, board of commissioner composition and audit committee) have significant effect toward earning quality, (2) corporate governance mechanism (managerial ownership, board of commissioner composition, audit committee) and earning quality have no significant effect toward value of the firm.Keyword: Corporate Governance Mechanism, Earning Quality and Value of the Firm